A FE study on the effect of interference fit and coefficient of friction on the micromotions and interface gaps of a cementless PEEK femoral component. (May 2022) - Post, Corine E.; Bitter, Thom; Briscoe, Adam; Verdonschot, Nico; Janssen, Dennis
Abstract: The use of a more compliant material, such as polyetheretherketone (PEEK), for a cementless femoral component is a potential solution to prevent aseptic loosening caused by peri-prosthetic stress-shielding. Long-term fixation of a cementless femoral component is achieved by a proper primary fixation of the bone-implant interface, which is influenced by the interference fit and frictional properties of the implant surface. This computational study investigates the sensitivity of micromotions and interface gaps of a cementless PEEK femoral component to the interference fit and coefficient of friction. 24 finite element models of the femur and femoral component were created with variations in implant material, interference fit and coefficient of friction. Peak loads of a jogging activity were applied on the models. Micromotions and interface gaps were both sensitive to the interference fit, coefficient of friction and implant material. Besides the implant material, the micromotions and interface gaps of the implant were most sensitive to the interference fit. Compared to the cobalt-chrome (CoCr) femoral component, the PEEK femoral component generated higher micromotions and interface gaps when equal interference fit and friction values were applied. However, increasing the interference fit and friction of the PEEK component resulted in micromotion values comparable with the CoCr component. This result leads to possibilities using cementless PEEK femoral components.